Spirulina supplement and exercise training affect lipid droplets-related genes expression in visceral adipose tissue - Fariba Shahandeh; Rozita Fathi; Khadijeh Nasiri (Mashhad University of Medical Sciences, 2024)
Objective: Disruption of lipid droplets (LDs) is associated with many metabolic diseases. Spirulina, as a natural bioactive dietary supplement, along with exercise training, may improve lipid metabolism; however, their effects on LDs-regulated genes in visceral adipose tissue are still unclear. This study aimed to investigate the effects of six-week Spirulina supplementation along with exercise training on LDs regulating gene expression.Materials and Methods: Fifty-six male Wistar rats were divided into six groups: saline (control), control+Spirulina (Spirulina), aerobic interval training (AIT), AIT+ Spirulina (AIT+Spirulina), resistance training and resistance+ Spirulina. The supplement groups consumed 500 mg/kg Spirulina five days per week. The training groups performed AIT (5 times per week) and resistance training (3 times per week) for 6 weeks. LDs regulating genes expression in visceral adipose tissue (Zw10, Bscl2, DFCP1, Rab18, Syntaxin 18, Acsl3, and Plin2) was analyzed by real-time PCR.Results: Spirulina and exercise training had no significant effects on the gene expression of Syntaxin18 (p=0.69) and DFCP1 (p=0. 84), ACSL3 (p=0.98), or BSCL2 (p=0.58). In addition, Spirulina was found to significantly attenuate the expression of Plin2 (p=0.01) and Rab18 (p=0.01) genes compared to the control, AIT, and resistance training groups. However, Plin2 gene expression was higher in the resistance training than the AIT. Furthermore, Spirulina decreased ZW10 (p=0.03) gene expression in visceral adipose tissue compared to the control, AIT, and resistance training groups. Unexpectedly, Spirulina supplementation decreased the expression of these genes even more when taken without exercise trainingConclusion: Spirulina supplementation and exercise training have significant effects on LDs-regulated genes in visceral adipose tissue.